The Effects of Classroom Interaction on Students’ Participation in English Learning Process at Mas Syekh Yusuf - Hartina Hamri; Murni Mahmud; Maemuna Rasyid (International Journal of Language, Education, and Literature, 2024)
Classroom interaction is essential in the learning process. However, not all the students willingly participate in classroom interaction, and the students do not even understand the teacher's question or know the answer. Thus, teachers' creativity and various ways of interaction are needed to form effective classroom interaction. This researcher aims to determine the effects of classroom interaction on students' participation in the English learning process. The researcher employed a descriptive qualitative design, and the data was collected through classroom observation and interviews. The results of this research show that classroom interaction positively affects the students' participation, such as influencing the students to raise their hand to solve the task to show the students' comprehension and attractiveness of the material, helping the students seek other classmates' opinions due to the students' confidence on their own opinion or have no courage to ask the teacher, helping the students in asking the question when the teacher' question or statement is unclear, stimulating the students in explaining simply because the student's comprehension and condition, challenging the students to contribute in the learning process because not all the students have confidence in putting contribution voluntarily. Based on the findings of this research, it can be concluded that classroom interaction positively affects the students' participation; thus, it is critical to the successful learning process. In addition, through classroom interaction, the students can be helped in the learning process and in improving the students' skills and self-confidence.